SIFAT KEPRIBADIAN SEBAGAI PEMODERASI HUBUNGAN STRES KERJA DAN PERILAKU DISFUNGSIONAL AUDIT - Rustiarini, Ni Wayan (UI Scholars Hub, 2014)
Auditor personality trait is an interesting topic in accounting field because this research is still rarely on accounting profession in Indonesia. The purpose of this study was to investigate the effect of work stress and dysfunctional audit behavior, with a focus on personality trait role: the big five personality and locus of control. The respondents for this study are auditors who work on public accounting firms in Bali. Moderated regressions analysis test used to examine seven hypotheses are formulated. The results showed that job stress have positive effects on dysfunctional audit behavior. Moreover it was determined that one of the personality trait, openness to experience, along with internal and external locus of control, have significant effect on the relation between job stress and dysfunctional audit behavior, but other personality traits such as conscientiousness, extraversion, agreeableness, and neuroticism do not have significant effect on the relation between job stress and dysfunctional audit behavior. This indicates that auditor personality is important to reduce the likelihood of dysfunctional audit behaviors.